Behavior coaching and social reciprocity and propriety among adolescents with autism - Valderrama, Johann Carl Barruga (College of Education, University of the Philippines Diliman, 2020)
While behavior intervention programs have been proven to improve social functioning among people with disabilities, only a few studies have focused specifically on behavior coaching. The study examined some aspects of the behavior coaching program and its impact on the social reciprocity and propriety of five adolescents with autism (AA). Data collection for small-group case study involved comparing previous and present records of these adolescents, observing actual behavior coaching sessions, and interviewing the parents and caregivers of the AA. Results revealed that the AA showed improved social reciprocity and propriety through the behavior coaching program. Specifically, aspects of the behavior coaching program related to the adolescents themselves, their coaches, and their home environment were pound to impact social reciprocity and propriety. Results also showed that the achievement of present social reciprocity and propriety goals was contingent on the duration and contextual implementation of and specific approaches employed through the behavior coaching program, particularly community integration.